Comparison of T cell response to vaccination in rheumatic patients treated with Janus kinase inhibitors and TNF inhibitors - Sebastian Hüper; Florian Eisele; Johannes Duell; Marc Schmalzing; Lea Nagler; Patrick Pascal Strunz; Matthias Froehlich; Jan Portegys; Michael Gernert (BMC Rheumatology)
Abstract Background Janus kinase inhibitors (JAKi) represent a well-established therapeutic option for the treatment of autoimmune diseases. However, there is a paucity of evidence regarding their impact on de novo immune responses to vaccinations. T cells may confer long-lasting immunity and cross-recognise evolving epitopes of new viral variants, as evidenced by the SARS-CoV-2 vaccination. Consequently, we investigated the de novo T-cell response to SARS-CoV-2 vaccination in patients with rheumatic diseases undergoing treatment with JAK inhibitors. Methods Cross-sectional study, conducted in an outpatient department. Patients with rheumatic disease who had received two vaccinations against SARS-CoV-2 while under therapy with JAKi (n = 22) or tumour necrosis factor-blocking biologicals (TNFi) (control group n = 16) were recruited. To evaluate the vaccine-induced T cell response, the patients’ PBMCs were stimulated with SARS-CoV-2 spike protein peptides. The percentage of CD4+ T cells responding specifically to this stimulation by producing IFNγ was then measured using intracellular cytokine staining and flow cytometry. In addition antibody response to vaccination was assessed. Results A specific T cell response was detected in 11 out of 22 (50.0%) of patients in the JAKi cohort, compared to 13 out of 16 (81.3%) of the TNFi cohort (p = 0.088). Patients on JAKi had a lower percentage of CD4+ T cells responding to stimulation with SARS-CoV-2 spike peptides than patients on TNFi (p = 0.021). The proportion of patients with an antibody response and absolute anti-spike IgG levels did not significantly differ between the cohorts. Conclusions Patients on JAKi exhibited a compromised de novo T cell response to SARS-CoV-2 vaccination compared to TNFi patients. There is a need for further research on the effect of JAKi on T cell responses to vaccination.